Master visually 3ds Max 8 - McFarland, Jon (Visual, 2006)
Navigating within the interface. Creating and editing 2D and 3D objects. Controlling animation with function curves. Integrating walls, doors and windows. Simulating water surfaces and fluttering flags. Adjusting color and brightness of lighting.Rendering scenes with Quick Render.